The threatening wave: Norse poetry and the Scottish Isles - Jesch, Judith (Maney Publishing, 2016)
The poetry discussed in this paper presents a range of responses to sailing around the northern parts of the British Isles, by poets more or less familiar with these routes but also with Norway, Iceland and sea-ways much further afield. These poets use traditional forms and imagery to express the pan-Norse identity of North Britain. At the same time they also give voice to what is distinctive about this region – its communities, its rulers, its language, its landscapes and seascapes, and, most particularly, the special challenges of sailing in these waters. The Norse poetry considered here expresses the specific maritime identities of Scandinavian Scotland, using the cultural frameworks of the broader Viking diaspora.